Role of TCTP in Cell Biological and Disease Processes - Bommer, Ulrich-Axel; Kawakami, Toshiaki (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Translationally controlled tumor protein (TCTP), also referred to as HRF or fortilin, is a multifunctional protein, expressed in all eukaryotic organisms from protozoa to humans. TCTP is involved in many basic biological processes, such as cell division, growth, and development. It is therefore not surprising that dysregulation of TCTP occurs in various disease processes, such as cardiovascular, allergic, and immune disorders. TCTP's role in cancer-promoting pathways is well- documented, and the protein is considered a potential target for the design of new anti-cancer strategies. Therefore, an understanding of the core biological functions of TCTP, the mechanisms underlying its cellular regulation, and its involvement in disease processes is important. This book provides a current overview on the basic biological functions of TCTP and on its role in promoting a range of disease processes.